The Slogan "Return to the Qur'an" in Indonesia: The Perspective of Ludwig Wittgenstein's Language Game - Novi Laila Athiyah; Aghnin Khulqi; Muhammad Rizal Mahfuzo (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2026)
Currently there are Muslim groups in Indonesia who always raise the slogan "Return to the Qur’an", in fact something like this has happened in the past, namely the tahkim or arbitration incident. These two phenomena still have the same common thread even though they occurred in different time, namely the opinion of back to the Koran. This paper aims to examine the phenomenon of language use in relation to the slogan "Return to the Qur’an" by certain Muslim groups and the tahkim event using the Language Game approach initiated by Ludwig Wittgenstein. This study is qualitative research using a literature review with an analytical descriptive model, namely describing in a straightforward manner the results of the conclusions from the data analysis carried out by the author. The findings in this research are that the slogan "Back to the Koran" is misused by radical and extremist groups for personal interest to gain validation for radicalism and extremism thoughts. It is similar to the Muawiyah group using this slogan opinion as a political step during the tahkim event.